2017
DOI: 10.1093/ehjci/jex186
|View full text |Cite
|
Sign up to set email alerts
|

Change in biventricular function after cone reconstruction of Ebstein’s anomaly: an echocardiographic study

Abstract: Although clinical outcome of Cone reconstruction for EA remains excellent, acute post-operative changes leads to reduction of myocardial function of both ventricles, with a trend to later recovery for LV. Continuing impairment of RV function is multifactorial but may reflect intrinsic myocardial deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Postoperative tricuspid regurgitation (TR) significantly improves after cone reconstruction, however, RV function typically does not improve until much later 6‐8 . Patients in the reported cohort who did poorly mostly had severe TR preoperatively, although this was not significant which may be related to a small sample size 5 .…”
Section: Commentarymentioning
confidence: 82%
“…Postoperative tricuspid regurgitation (TR) significantly improves after cone reconstruction, however, RV function typically does not improve until much later 6‐8 . Patients in the reported cohort who did poorly mostly had severe TR preoperatively, although this was not significant which may be related to a small sample size 5 .…”
Section: Commentarymentioning
confidence: 82%
“…Several plausible explanations are as follows: first, previous evidence [ 23 ] have indicated a concerning rise in SD risk triggered by the ventricular/atrial arrhythmias in the EA population. Delaying repair potentially exposes patients to the development of cardiomegaly and haemodynamic instabilities, which are the substrates giving rise to such arrhythmias; second, the echocardiographic [ 13 ] and cardiac magnetic resonance (CMR) [ 12 , 24 ] data have revealed sustainable improvement of biventricular function and remodelling after a successful EA surgery, which is crucial in maintaining sinus rhythm and atrioventricular synchrony. In addition, the risk of arrhythmias and SD increased over time [ 23 ], and data from the adult EA [ 25 ] indicated that earlier surgery could unburden the RV from the abnormal physiology and yield more favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In Ebstein's anomaly (EA), an accurate assessment of cardiac chamber size and function is essential for risk stratification and management decisions before significant cardiomegaly or functional deterioration develops. 134,135 However, RV size and function can be difficult in EA due to the complex RV geometry, the presence of an atrialized RV, variable chamber dilation, and masked RV dysfunction secondary to volume overload. 136 The accurate echocardiographic assessment of RV size is limited due to the abnormal RV geometry.…”
Section: Volume-loaded Rvmentioning
confidence: 99%